Impact of Spirituality at Work on Organizational Commitment - Srimulyani, Veronika Agustini; Hartanto, Feliks Kusuma Putra (Politeknik Piksi Ganesha Indonesia, 2025)
This study focuses on the study of the relationship between three dimensions of workplace spirituality, namely meaningful work, a sense of community, and alignment with organizational values with organizational commitment, using 60 employees of CV Cahaya Surya as a research sample. Data collection was carried out by distributing questionnaires directly to respondents. The research sample consisted of 60 employees. Hypothesis testing used path analysis with the Smart PLS version 3 program. From the results of the path analysis, it was reported that the dimensions of meaningful work and a sense of community had a positive and significant relationship. In contrast, the relationship between alignment with organizational values and organizational commitment was moderated by a sense of community. This study provides an important understanding that workplace spirituality can encourage the growth of organizational commitment as seen from three dimensions: affective, normative, and continuance.